Does education level affect the efficacy of a community based salt reduction program? - A post-hoc analysis of the China Rural Health Initiative Sodium Reduction Study (CRHI-SRS). (December 2016) - Wang, Xin; Li, Xian; Vaartjes, Ilonca; Neal, Bruce; Bots, Michiel; Hoes, Arno; Wu, Yangfeng
Abstract Background Whether educational level influences the effects of health education is not clearly defined. This study examined whether the impact of a community-based dietary salt reduction program was affected by the level of education of participants. Methods The China Rural Health Initiative Sodium Reduction Study (CRHI-SRS) was a cluster-randomized controlled trial conducted in 120 villages from five Northern Chinese provinces. The intervention comprised a village-wide health education program and availability of salt substitute at village shops. 24-h urine samples were collected among 1903 participants for primary evaluation of the intervention effect. A post-hoc analysis was done to explore for heterogeneity of intervention effects by education level using generalized estimating equations. All models were adjusted for age, sex, body mass index and province. Results Daily salt intake was lower in intervention than in control at all educational levels with no evidence of a difference in the effect of the intervention across different levels of education.P value for the interaction term between education level and the intervention was 0.35. There was likewise no evidence of an interaction for effects of the intervention on potassium intake (p = 0.71), the sodium to potassium ratio (p = 0.07), or knowledge and behaviors related to salt (allp > 0.05). Conclusions The study suggests that the effects of the intervention were achieved regardless of the level of education and that the intervention should therefore be broadly effective in rural Chinese populations. Trial registration The trial was registered with clinicaltrial.gov (NCT01259700 ).